Optimizing EAI with AI and Cloud-Native Platforms : A Comparative Study of Popular Integration Frameworks - Umamaheswarareddy Chintam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of artificial intelligence with cloud-native platforms represents a transformative approach to Enterprise Application Integration, offering enhanced efficiency, scalability, and adaptability for modern businesses. This article examines the role of AI in optimizing EAI processes, with particular focus on its implementation across major cloud-native integration frameworks including SAP Cloud Platform Integration, MuleSoft, and Apache Camel. Through comparative analysis, this article evaluates how AI capabilities are embedded within these platforms to enhance data processing, workflow orchestration, and automation. It provides insights into the strengths and limitations of each framework regarding AI integration, usability, scalability, and performance metrics, offering valuable guidance for organizations seeking to leverage AI and cloud-native technologies for their integration needs.
Keywords: Enterprise Application Integration; Artificial Intelligence; Cloud-Native Platforms; Integration Frameworks; Digital Transformation